The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/8105087
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Exposure to Sexually Explicit Materials and Substance Abuse among High-School Adolescents in North Shewa Zone: Application of Logistic Regression Analysis

Abstract: Background. The use of substances such as cigarettes, khat, alcohol, and other illicit drugs like hashish, heroine, cannabis, and cocaine is a global major public threat, which affects young adult people particularly in developing countries. This study aims to assess the risk factors associated with substance use and exposure to sexually explicit materials among high-school adolescents in north Shewa zone, Oromia region. Method. A cross-sectional study was conducted to assess substance use and exposure to sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…A strong finding of our study was the consistent existence of significant gender effects across participating countries, replicating a finding of previous research [21,28,29,[36][37][38][39][40]. A much higher proportion of adolescent males than females reported exposure to pornography in the last 12 months, and this pattern held true for both any/occasional exposure and frequent exposure.…”
Section: Gender and Age Effects On Exposuresupporting
confidence: 87%
See 1 more Smart Citation
“…A strong finding of our study was the consistent existence of significant gender effects across participating countries, replicating a finding of previous research [21,28,29,[36][37][38][39][40]. A much higher proportion of adolescent males than females reported exposure to pornography in the last 12 months, and this pattern held true for both any/occasional exposure and frequent exposure.…”
Section: Gender and Age Effects On Exposuresupporting
confidence: 87%
“…Adolescents' exposure to pornography is influenced by a range of developmental, social, demographic, psychological, and educational factors. Most studies have shown that male adolescents used pornography more often than their female counterparts [3,21,32,33,[36][37][38][39][40][41][42]. However, gender differences in exposure to pornography were not shown in more liberal countries [38,[43][44][45].…”
Section: Factors Associated With Adolescents' Pornography Exposurementioning
confidence: 99%
“…Respondents coming from an area where substance is commonly used were found an associated factors for substance use which is similar to other studies conducted at Jimma University medical interns (15,32).Under this study, having a friend who uses a substance is signi cantly associated (p < 0.05) with current substance use which is supported by other two studies conducted in Jimma (15,32). Moreover, the study conducted among at north Shewa high school adolescent students indicated that friend substance use experience had an effect on starting substance (30).Overall, this study revealed that substance abuse was found common among intern and resident medical students at the University of Gondar. The magnitude of this prevalence was comparably similar to other studies.…”
Section: Declarationssupporting
confidence: 88%
“…Enjoyment (39%) was a major reason for starting substance use which is consistent with the study done in central Ethiopia and the prevalence of alcohol taking, khat chewing, and cigarette smoking was higher than the study done at Debre berhan undergraduate students (28).This difference may be because the study participants at Debre berhan were at all students level but in the current study setting medical students were the only respondents all may be passing through learning and social stress due to extended class schedule and lower than the study conducted at American medical students (91%) (29).Under this study, age was an associated factor for substance use which is inconsistent with the study conducted at Jimma University medical interns (15).This inconsistency may be due to study area setting differences resulting in environmental and family background variation. In other studies age was found a signi cantly associated with substance use (30)In addition, family history of substance use had association with current substance use which is also found a predictor by two other studies (15,31).…”
Section: Declarationsmentioning
confidence: 59%
“…This study was also found to be high when compared to previous studies done in Ethiopia's urban and rural areas (3%), Bale (4.6%), Shewa (4.5%), Northwest Ethiopia (6.8%), and Eastern Africa (9.02%). [22][23][24][25][26] Previous studies were conducted in academic institutions such as high schools, colleges, and universities. In addition, this study was conducted in eastern Ethiopia, where khat chewing and tobacco use are common, and our study was a population-based study that only included adolescents from the urban.…”
Section: Discussionmentioning
confidence: 99%